Assessing direct and indirect economic impacts of a flood event through the integration of spatial and computable general equilibrium modelling. (January 2015) - Carrera, Lorenzo; Standardi, Gabriele; Bosello, Francesco; Mysiak, Jaroslav
Abstract: In this paper we developed and tested an integrated methodology for assessing direct and indirect economic impacts of flooding. The methodology combines a spatial analysis of the damage to the physical stock with a general economic equilibrium approach using a regionally-calibrated (to Italy) version of a Computable General Equilibrium (CGE) global model. We applied the model to the 2000 Po river flood in Northern Italy. To account for the uncertainty in the induced effects on regional economies, we explored three disruption and two recovery scenarios. The results highlight that: i) the flood event produces indirect losses in the national economic system, which are a significant share of the direct losses, and ii) the methodology is able to capture both positive and negative economic effects of the disaster in different areas of the same country. The assessment of indirect impacts, in particular, is essential for a full understanding of the economic outcomes of natural disasters. Highlights: Rarely the accounting of flood losses includes indirect economic impacts. The proposed method integrates spatial and computable general equilibrium modelling for the estimation of indirect impacts. We analyse a flood event in Northern Italy, reporting indirect economic impacts as around 20 percent of direct impacts. Economic benefits arise in non-flooded sub-regions of Italy.